Dolina Triglavskih jezer - Brancelj, Anton (Geografija Slovenije, 2015)
In 1924, the Triglav Lakes Valley was designated a protected area, which is today part of the central area of extensive Triglav National Park. The lakes give a special character to the valley, which also stands out for its other natural features. In terms of nonliving nature, this volume presents some of the valley's geological, geomorphological, and hydrological characteristics, and, in terms of living nature, it presents its vegetation, focusing on botanical characteristics and forest. The volume also discusses the human presence and its impact on the appearance of the landscape.